Clinical Assessment and Brain Findings in a Cohort of Mothers, Fetuses, and Infants Infected With ZIKA Virus. Issue 1 (March 2019) - Sanz Cortes, M.; Rivera, A.M.; Yepez, M.; Guimaraes, C.V.; Diaz Yunes, I.; Zarutskie, A.; Davila, I.; Shetty, A.; Mahadev, A.; Serrano, S.M.; Castillo, N.; Lee, W.; et al.
Abstract : ( Am J Obstet Gynecol . 2018;218:440.e1–e36) Perinatal infection of women with Zika virus (ZIKV) results in congenital ZIKV syndrome (CZS) in 10% of cases. CZS results in brain and ocular malformations, microcephaly, congenital deafness, limb contractures, and arthrogryposis. However, there is lack of consensus regarding the diagnosis and prognosis of CZS, and screening recommendations for the detection of fetuses affected by CZS range from screening for microcephaly alone to a full neuroanatomic evaluation. The objectives of the current study were (1) to assess the prevalence of microcephaly and other brain findings in infected and affected fetuses and infants, (2) to compare these findings with other congenital ZIKV series reported to date, and (3) to provide quantitative measures of magnetic resonance imaging (MRI) of fetal and infant brain imaging.